2016
DOI: 10.2337/dc16-1145
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Duration of Depressive Disorders in Patients With Type 2 Diabetes

Abstract: OBJECTIVEDepression in patients with type 2 diabetes (T2D) is associated with long-term complications, disability, and early mortality. No studies have systematically examined the length of episodes and remission in adults with major depressive disorder (MDD) and T2D. This study examined the course of depressive disorders in patients with T2D and MDD.RESEARCH DESIGN AND METHODSParticipants (N = 50) enrolled in a behavioral intervention for adults with T2D and MDD were interviewed using the Structured Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 40 publications
3
16
0
3
Order By: Relevance
“…We identified differences in the prevalence of depressive symptoms, as well as the clinical diagnosis of depression among the countries. Consistent with other studies, we found significant links between MDD and diabetes complications, although the latter was a stronger predictor in the moderate/severe depressive symptomatology model [29,30]. The results of the present study showing significant multivariable associations of current MDD diagnosis with demographic and psychosocial variables are generally consistent with those of other cross-sectional studies carried out in the UK and USA using self-reported symptoms of depression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We identified differences in the prevalence of depressive symptoms, as well as the clinical diagnosis of depression among the countries. Consistent with other studies, we found significant links between MDD and diabetes complications, although the latter was a stronger predictor in the moderate/severe depressive symptomatology model [29,30]. The results of the present study showing significant multivariable associations of current MDD diagnosis with demographic and psychosocial variables are generally consistent with those of other cross-sectional studies carried out in the UK and USA using self-reported symptoms of depression.…”
Section: Discussionsupporting
confidence: 92%
“…Although measures differ across studies, depression, whether assessed by self-reported symptoms or by diagnostic interviews, has been found to be strongly associated with gender, lower education level [26,27], physical inactivity [28] and previous depression [27]. Consistent with other studies, we found significant links between MDD and diabetes complications, although the latter was a stronger predictor in the moderate/severe depressive symptomatology model [29,30]. Mean age and BMI in the present study were comparable with data from other multinational studies such as the DAWN2 study [31]; however, the percentage of people treated with insulin was higher in the present study than in the DAWN2 study, which may be explained by the fact that participants in the latter study were stratified by type of treatment, while the present study only included participants from secondary care, who are more likely to be treated with insulin.…”
Section: Discussionsupporting
confidence: 87%
“…Race/ethnicity and age, as well as dietary intakes of nutrients and physical activity known to influence glycaemia and insulin action dynamics, will be controlled for in the linear mixed models. Since other outcomes including sleep [66] and mood disturbances [67] may affect study outcomes, we may include these in the model. Continuous data will be tested for normality and if the data is skewed, log transformation may be used to normalize data or non-parametric statistics will be used.…”
Section: Methodsmentioning
confidence: 99%
“…These articles also represent work conducted with samples across the life span ranging from the experiences with artificial pancreas in children with type 1 diabetes and their parents (7) to adult couples with type 2 diabetes (8). Three articles address the emotional and affective experience of diabetes by examining 1 ) stigma associated with type 2 diabetes (5), 2 ) the course of depressive disorders in adults with type 2 diabetes (9), and 3 ) linkages between emotional distress and self-care behaviors (10). Additional work examines the use of an Internet platform to deliver a behavioral intervention to address hypoglycemic unawareness in adults with type 1 and type 2 diabetes using insulin (11).…”
mentioning
confidence: 99%
“…While depressive episodes have been documented to be recurrent (15) and depressive symptoms persistent (16,17), the naturalistic course of depression in adults with type 2 diabetes has been understudied. In this issue, de Groot et al (9) examine the course of clinical depressive disorders in a well-characterized cohort of 50 adults with type 2 diabetes using a diagnostic psychiatric interview protocol. This article is the first to document the duration and pattern of recurrent depressive disorders from birth to date of study completion.…”
mentioning
confidence: 99%